Molecular dynamics simulation and experimental verification of the crystallization behavior of a Ti–Zr–Ni alloy prepared by SPS low temperature liquid phase sintering. (December 2022) - Luo, Shuyi; Luo, Junting; Kang, Qingxin; Li, Zhenlun; Wang, Guofeng
Abstract: Titanium-zirconium (Ti–Zr)alloys have attracted more and more research attention due to their excellent mechanical properties and corrosion resistance. Herein, molecular dynamics simulation is used to study the relationship between the solid-liquid phase transition temperature, the content of each phase, and the growth anisotropy of the β phase under various sintering temperatures and cooling rates during the crystallization process of the Ti–Zr–Ni alloy. Using GH4169 alloy powder as an additive, Ti–Zr–Ni alloy samples with fine grains are prepared via spark plasma sintering (SPS) technology, and their crystallization and microstructural evolution are characterized by electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). The results show that: (i) when the cooling rate is greater than the critical cooling rate of the first-order phase transformation, the regular face centered cubic-hexagonal close packed (FCC-HCP) structure is significantly replaced by an increasing content of amorphous structure, and (ii) with the increase in sintering temperature, the critical cooling rate of the completely amorphous state increases gradually, and the growth rates of the matrix in (001) and (111) directions are fast, thereby resulting in anisotropic growth. Highlights: As the sintering temperature increases, the potential energy of the system increases, and complete amorphous occurs. When the cooling rate is greater than the critical cooling rate of the completely amorphous phase, the contents of amorphous structure increase significantly. The precipitation orientation of the α transition phase is close to the < 11 2 − 0 > orientation, and the β phase is preferentially precipitated along the rotated cubic orientation ((100)[011]). The matrix anisotropy results obtained by EBSD are consistent with the simulation results, i.e., the matrix growth rate has obvious anisotropy.